2022
DOI: 10.1177/02692155221143865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapeutic interventions on pain due to plantar fasciitis: A systematic review and meta-analysis

Abstract: Objective To determine the effects of different therapeutic interventions that have ever been evaluated in randomized controlled trials on pain due to plantar fasciitis. Methods We searched different electronic databases until September 2022. Mean differences (MDs) and 95% confidence intervals (CIs) were calculated. The Grading of Recommendations Assessment, Development and Evaluation was used to evaluate the overall certainty evidence. Results A total of 236 studies met the study criteria, including 15,401 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 234 publications
0
14
0
Order By: Relevance
“…We included 17 publications in this map covering 13 health conditions. 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 The literature flowchart ( Figure 1 ) summarizes results of the study selection process, and eAppendix 2 in Supplement 1 presents citations for all excluded reviews at full-text screening.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included 17 publications in this map covering 13 health conditions. 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 The literature flowchart ( Figure 1 ) summarizes results of the study selection process, and eAppendix 2 in Supplement 1 presents citations for all excluded reviews at full-text screening.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of primary studies about massage therapy for pain in the included reviews ranged from 2 studies to 23 studies. There were 12 reviews that included fewer than 10 primary studies 4 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 and 5 reviews that included 10 to 25 studies about massage therapy for pain. 10 , 18 , 19 , 24 , 25 Of included reviews, 3 reviews were completed by the Cochrane Collaboration 4 , 19 , 23 and 2 reviews were completed by the AHRQ EPC program.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical guidelines recommend different treatment interventions, e.g., corticosteroid injection, exercises, extracorporeal shockwave therapy, or manual therapies for plantar heel pain [3,4]; however, current evidence on which treatment strategy is the most effective is inconclusive [5]. Two meta-analyses have found that needling interventions are effective for managing plantar heel-associated pain [6] but highlighted the need for further research on their efficacy and the methodology used to perform these interventions.…”
Section: Introductionmentioning
confidence: 99%